Percutaneous Endoscopic Posterior Lumbar Interbody Fusion with Unilateral Laminotomy for Bilateral Decompression Vs. Open Posterior Lumbar Interbody Fusion for the Treatment of Lumbar Spondylolisthesis - He, Li-Ming; Li, Jia-Rui; Wu, Hao-Ran; Chang, Qiang; Guan, Xiao-Ming; Ma, Zhuo; Feng, Hao-Yu (Frontiers in Surgery, 2022)
Abstract Background: Endoscopic lumbar interbody fusion is a new technology that is mostly used for single-segment and unilateral lumbar spine surgery. The purpose of this study was to introduce percutaneous endoscopic posterior lumbar interbody fusion (PE-PLIF) with unilateral laminotomy for bilateral decompression (ULBD) for lumbar spondylolisthesis and evaluate the efficacy by comparison with open posterior lumbar interbody fusion (PLIF). Methods: Twenty-eight patients were enrolled in the PE-PLIF with ULBD group and the open PLIF group. The perioperative data of the two groups were compared to evaluate the safety of PE-PLIF with ULBD. The visual analog scale (VAS) back pain, VAS leg pain and Oswestry Disability Index (ODI) scores of the two groups preoperatively and postoperatively were compared to evaluate clinical efficacy. Preoperative and postoperative imaging data were collected to evaluate the effectiveness of the operation. Results: No differences in baseline data were found between the two groups (P>0.05). The operation time in the PE-PLIF with ULBD group (221.2±32.9 min) was significantly longer than that in the PLIF group (138.4±25.7 min) (P<0.05), and the estimated blood loss and postoperative hospitalization were lower than those of the PLIF group (P<0.05). The postoperative VAS and ODI scores were significantly improved in both groups (P<0.05), but the postoperative VAS back pain score in the PE-PLIF group was significantly lower than that in the PLIF group (P<0.05). The excellent and good rates in both groups were 96.4% according to MacNab’s criteria. The disc height and cross-sectional area of the spinal canal were significantly improved in the two groups after surgery (P<0.05), with no difference between the groups (P>0.05). The fusion rates in the PE-PLIF with ULBD group and PLIF group were 89.3% and 92.9% (P>0.05), respectively, the cage subsidence rates were 14.3% and 17.9% (P>0.05), respectively, and the lumbar spondylolisthesis reduction rates were 92.72±6.39% and 93.54±5.21%, respectively (P>0.05). Conclusions: The results from this study indicate that ULBD can be successfully performed during PE-PLIF, and the combined procedure is a safe and reliable treatment method for lumbar spondylolisthesis.